Endometrial Cancer Immune Escape Mechanisms: Let Us Learn From the Fetal–Maternal Interface - Bruno, Valentina; Corrado, Giacomo; Baci, Denisa; Chiofalo, Benito; Carosi, Maria Antonia; Ronchetti, Livia; Piccione, Emilio; Albini, Adriana; Noonan, Douglas M.; Piaggio, Giulia; Vizza, Enrico (Frontiers in Oncology, 2020)
The immune escape mechanisms at the base of tumor progression in endometrial cancer mimic immune tolerance mechanisms occurring at maternal-fetal interface. The biological and immunological processes behind maternal-fetal interface are finely tuned in time and space during embryo implantation and subsequent pregnancy stages, conversely those behind cancer progression are often aberrant. The environment composition at the maternal-fetal interface parallels with pro-tumor microenvironment identified in many cancers, pointing the possibility for the use of maternal fetal interface as a model to depict immune therapeutic targets in cancer. The framework of cancer environment signatures involved in immune adaptations, precisely timed in cancer progression, could reveal a specific “immune clock” in endometrial cancer, which might guide clinicians in patients risk class assessment, diagnostic work-up, management, surgical and therapeutic approach and surveillance strategies. Here, we review studies approaching this hypothesis focusing on what is known so far about onco-fetal similarities in immunity with the idea to individualize personalized immunotherapy targets, through the down-regulation of the immune escape stage or the reactivation of the pro-inflammatory processes suppressed by the tumor.